2022
DOI: 10.3389/fpsyg.2022.814633
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of High-Intensity Aerobic Exercise on Motor Cortical Excitability and Inhibition in Sedentary Adults

Abstract: Transcranial magnetic stimulation studies have demonstrated increased cortical facilitation and reduced inhibition following aerobic exercise, even when examining motor regions separate to the exercised muscle group. These changes in brain physiology following exercise may create favorable conditions for adaptive plasticity and motor learning. One candidate mechanism behind these benefits is the increase in brain-derived neurotropic factor (BDNF) observed following exercise, which can be quantified from a veno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
3
12
0
Order By: Relevance
“…We observed that serum BDNF levels increased significantly relative to pre-exercise levels whether participants performed 1 min for 15 bouts or 2 min for 10 bouts of HIIT interventions. Which is consistent with previous study in humans ( Saucedo Marquez et al, 2015 ; Cabral-Santos et al, 2016 ; Martínez-Díaz et al, 2020 ; Tsai et al, 2021 ; Hendy et al, 2022 ). Although the training duration of the two HIIT protocols was different, with maximum levels of serum BDNF being observed toward the end of intervention.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We observed that serum BDNF levels increased significantly relative to pre-exercise levels whether participants performed 1 min for 15 bouts or 2 min for 10 bouts of HIIT interventions. Which is consistent with previous study in humans ( Saucedo Marquez et al, 2015 ; Cabral-Santos et al, 2016 ; Martínez-Díaz et al, 2020 ; Tsai et al, 2021 ; Hendy et al, 2022 ). Although the training duration of the two HIIT protocols was different, with maximum levels of serum BDNF being observed toward the end of intervention.…”
Section: Discussionsupporting
confidence: 94%
“…Which is consistent with previous study in humans (Saucedo Marquez et al, 2015;Cabral-Santos et al, 2016;Martínez-Díaz et al, 2020;Tsai et al, 2021;Hendy et al, 2022). Although the training duration of the two HIIT protocols was different, with maximum levels of serum BDNF being observed toward the end of intervention.…”
Section: Figuresupporting
confidence: 92%
“…According to the RoB 2.0 Cochrane tool, 24 one study scored at "low risk of bias", 55 four studies scored at "high risk of bias", 19,43,48,50 whereas the remaining 17 studies rated "some concerns" 20,[38][39][40][41][42][44][45][46][47]49,[51][52][53][54]56,57 (Figure S1). By domain, the randomization process was the highest rated as "high risk of bias" (13.6%), and the selection of the reported outcome was the highest rated as "some concerns" (81.8%).…”
Section: Risk Of Biasmentioning
confidence: 99%
“…The length of the exercise programs, in which the chronic effect of training was evaluated, ranged from 3 to 12 weeks, and the frequency ranged from 2 to 5 days per week, prevailing 3 days per week in eight studies. 19,39,[41][42][43]45,47,52 HIIT sessions were performed primarily on cycle ergometer in 10 studies, 20,[39][40][41]44,45,47,51,52,55 followed by treadmill in seven studies, 19,38,42,43,48,49,57 seated stepper in one study, 57 one study in a Speedflex machine, 56 lower body ergometer in one study, 45 different types of exercises (squat jump, inchworm, walk down-shoulder tap, plank get ups, goblet squats, jackknife crunch, and burpee mountain climbing movements) in one study 54 and various aerobic exercise equipment (e.g., treadmill, cycle ergometer, elliptical, etc.) or dance/movement-based routines in one study.…”
Section: Interventionmentioning
confidence: 99%
“…High intensity aerobic exercise in particular can also improve motor skill acquisition in neurologically intact people (Skriver et al ., 2014; Stavrinos & Coxon, 2017; Dal Maso et al ., 2018; Kendall et al ., 2020), and individuals with chronic stroke (Nepveu et al ., 2017). These improvements are linked to a decrease in the neurotransmitter gamma-aminobutyric acid (Singh et al ., 2014; Singh & Staines, 2015; Stavrinos & Coxon, 2017; Hendy et al ., 2022), and an increase in the protein brain-derived neurotrophic factor (Sleiman et al ., 2016), both of which play important roles in neuroplasticity (Stagg et al ., 2011; Mang et al ., 2013; Andreska et al ., 2020). Therefore, beyond the potential cognitive benefits associated with high intensity aerobic exercise, pairing it with motor rehabilitation is a promising method to enhance cognitive-motor function.…”
Section: Introductionmentioning
confidence: 99%